Psychosocial factors associated with speech perception in older adult cochlear implant users: a scoping review - Anderson, Ilona; Angerer-Klaunzer, Katharina; Opie, Jane (Frontiers in Neuroscience, 2025)
BackgroundThe population of older adults (OAs) is significantly increasing, and with that is the reality of OAs having hearing loss (HL). Although there is no hearing screening for adults, some OAs do consult their audiologist or otologist and receive a cochlear implant (CI). There are several studies showing that CI surgery in OAs is safe, and post-CI speech perception is similar to younger adults. However, there is little knowledge about what psychosocial factors may be associated with speech perception outcomes in OAs. The objective of this scoping review is to address these open questions.MethodsThis scoping review was conducted in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. PubMed and the Cochrane Library were searched for studies in English and German published between Jan 2020 and Jan 2025 reporting on psychosocial factors relating to speech perception outcomes in OAs with CIs.Results6/94 studies met the inclusion criteria. The six included publications considered the associations of quality of life, frailty, depression, and family support on speech perception in OAs with CIs. The association between these factors and sound perception was variable.ConclusionAlthough CIs are not uncommon as a treatment for HL in OAs, few studies have addressed the associations of psychosocial factors with speech perception in this population, or vice versa. More research needs to be conducted to determine these psychosocial factors and their impact on speech perception to better care for OAs with CIs.